2019
DOI: 10.1016/j.actamat.2019.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical behavior of ultrafine-grained aluminum-iron alloy stabilized by nanoscaled intermetallic particles

Abstract: Ultrafine-grained aluminum alloys offer interesting multifunctional properties with a combination of high strength, low electrical resistivity, and low density. However, due to thermally induced grain coarsening, they typically suffer from an intrinsic poor thermal stability. To overcome this drawback, an Al-2%Fe alloy has been selected because of the low solubility of Fe in Al and their highly positive enthalpy of mixing leading to the formation of stable intermetallic particles. The two-phase alloy has been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…In the Al-Ca composite before SPD, there are two phases: the fcc Al matrix and elongated submicrometer fcc Ca filaments [37]. These two phases are ductile and easily co-deform during the HPT process, which is the main difference with as-cast structures containing brittle intermetallic particles [19,[28][29][30]. During the early stage of deformation (one revolution by HPT), only a smooth hardness gradient appears (Fig.…”
Section: Influence Of Calcium On the Deformation Induced Nanoscaled Smentioning
confidence: 99%
See 1 more Smart Citation
“…In the Al-Ca composite before SPD, there are two phases: the fcc Al matrix and elongated submicrometer fcc Ca filaments [37]. These two phases are ductile and easily co-deform during the HPT process, which is the main difference with as-cast structures containing brittle intermetallic particles [19,[28][29][30]. During the early stage of deformation (one revolution by HPT), only a smooth hardness gradient appears (Fig.…”
Section: Influence Of Calcium On the Deformation Induced Nanoscaled Smentioning
confidence: 99%
“…However, the influence of segregations, both on electrical resistivity and mechanical strength of nanostructured Al alloys is not yet completely understood. It has already been demonstrated that grain refinement and intermetallic fragmentation can be successfully achieved by SPD processing of as-cast Al alloys containing immiscible elements (Rare Earth [28], Fe [19,29] or Ca [30]). However, starting from as-cast structures with intermetallic compounds requires huge plastic strains, and only Zener pinning can be achieved.…”
Section: -Introductionmentioning
confidence: 99%
“…There are situations where SPD leads to mechanical mixing and the formation of super saturated solid solutions in multi-phase metallic alloys, 57,58) but there are also situations where super saturated solid solutions decompose during SPD. 41,42,59,60) In the latter case, the initial material is single phase and the super saturated solid solution is usually obtained by quenching from high temperature where it is stable.…”
Section: Connection With Strain Induced Precipitationmentioning
confidence: 99%
“…Indeed, in such materials the driving force for grain growth is intrinsically large, thus if enough mobility is provided, grains will coarsen and the mechanical strength decreases. However, an enhanced thermal stability could be achieved if GBs are pinned by particles (so-called Zener pinning) 58) or segregations. 25) Besides, equilibrium GB segregations are driven by a minimization of the GB energy, thus they could help also stabilizing UFG or nanocrystalline structures by reducing the driving force for grain growth.…”
Section: Influence Of Strain Induced Segregations On Mechanical Propementioning
confidence: 99%
See 1 more Smart Citation